MEDIA DAN SUMBER BELAJAR IPS BAGI ANAK USIA SD/MI - Hasanah, Uswatun (IJTIMAIYA: Journal of Social Science and Teaching, 2018)
In general, the process of formal learning in all levels including elementary school is to use direct communication or spoken language. The ability of a teacher in spoken language is the most important aspect that must be owned by the teacher. However, psychological learning in elementary school requires concrete information, clearly not verbalistic, simple and requires a more enjoyable learning. The media has implications for the role and competence of teachers. Professional teachers should understand and have technical skills in creating and using the learning media. Each teacher is expected to be skilled in developing media and learning resources in IPS classroom activities.Keywords: Media, Learning Resources, IPS